2022
DOI: 10.1097/md.0000000000032250
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic influence for hilar cholangiocarcinoma and comparisons of prognostic values of Mayo staging and TNM staging systems

Abstract: The study was designed to discuss the effect of stratification factors in the Mayo staging on the prognosis of hilar cholangiocarcinoma (HCCA) patients, and to evaluate the predictive value of the Mayo staging on the prognosis. The Kaplan–Meier survival curve and Log-rank test were used to perform univariate analysis on each index and obtain statistically significant influencing factors. The Kaplan–Meier survival curve and Log-rank test were used to analyze the correlation between the two staging systems and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Also, lymph node involvement is an important factor as a further independent predictor of the outcome (22). At the current time, the widely used TNM-staging system and also the Mayo-staging system are enabling preoperative patient prognosis assessment, although the analysis of their prognostic capabilities just have been reported of wielding areas under the curve of only 0.50 and 0.59, respectively (23). Therefore, there is de nte need for better characterization of these patients and to provide novel prognostic biomarkets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, lymph node involvement is an important factor as a further independent predictor of the outcome (22). At the current time, the widely used TNM-staging system and also the Mayo-staging system are enabling preoperative patient prognosis assessment, although the analysis of their prognostic capabilities just have been reported of wielding areas under the curve of only 0.50 and 0.59, respectively (23). Therefore, there is de nte need for better characterization of these patients and to provide novel prognostic biomarkets.…”
Section: Discussionmentioning
confidence: 99%
“…Another work group performed a radiomics study on presurgical MRI and found that a combined clinical and radiomics based nomogram performed signi cantly better in the prediction of 1-, 3-and 5-year survival than the classical TNM-staging system [23]. When comparing the different nomograms, the combined clinical and radiomic approach performed only slightly better than the radiomic nomogram, although with no statistical signi cant difference.…”
Section: Discussionmentioning
confidence: 99%